Safer primary healthcare facilities are needed to protect healthcare workers and maintain essential services: lessons learned from a multicountry COVID-19 emergency response initiative. Issue 6 (3rd June 2021) - Patel, Leena N; Kozikott, Samantha; Ilboudo, Rodrigue; Kamateeka, Moreen; Lamorde, Mohammed; Subah, Marion; Tsiouris, Fatima; Vorndran, Anna; Lee, Christopher T
Abstract : Healthcare workers (HCWs) are at increased risk of infection from SARS-CoV-2 and other disease pathogens, which take a disproportionate toll on HCWs, with substantial cost to health systems. Improved infection prevention and control (IPC) programmes can protect HCWs, especially in resource-limited settings where the health workforce is scarcest, and ensure patient safety and continuity of essential health services. In response to the COVID-19 pandemic, we collaborated with ministries of health and development partners to implement an emergency initiative for HCWs at the primary health facility level in 22 African countries. Between April 2020 and January 2021, the initiative trained 42 058 front-line HCWs from 8444 health facilities, supported longitudinal supervision and monitoring visits guided by a standardised monitoring tool, and provided resources including personal protective equipment (PPE). We documented significant short-term improvements in IPC performance, but gaps remain. Suspected HCW infections peaked at 41.5% among HCWs screened at monitored facilities in July 2020 during the first wave of the pandemic in Africa. Disease-specific emergency responses are not the optimal approach. Comprehensive, sustainable IPC programmes are needed. IPC needs to be incorporated into all HCW training programmes and combined with supportive supervision and mentorship. Strengthened data systems on IPC are needed to guide improvements at the health facility level and to inform policy development at the national level, along with investments in infrastructure and sustainable supplies of PPE. Multimodal strategies to improve IPC are critical to make health facilities safer and to protect HCWs and the communities they serve.